The efficiency of using the ‘learning cycle’ strategy in acquiring Arabic grammatical concepts: a study applied to grade-nine students in Jordan - Al-Hawamdeh, Mohammad Fuad; Ashour, Rateb Qasem (Penerbit UKM, 2015)
Applied to grade 9 students in Jordan, this study aimed at examining the effi ciency of using the ‘learning cycle’ strategy in acquiring Arabic grammatical concepts. A sample of 124 students was approved, which was distributed over two schools (boys and girls) and in two groups. The experimental group was taught the subject instructional material through the learning cycle strategy with 29 males and 35 females, whereas the control group was taught through the same material through the traditional program with 32 males and 28 females. In terms of fi ndings, there were found statistically signifi cant differences in the subjects’ achievement in acquiring Arabic grammatical concepts, in favor of the experimental group. Statistically signifi cant differences were also found due to gender in favor of females. Whereas no statistically signifi cant differences were found due to the interaction between group/teaching strategy and gender.